Nurses’ ethical competence during the COVID-19 pandemic: Qualitative perspectives - Byun, Hye Min (Nursing ethics, 2025)
BackgroundEthical challenges and moral uncertainty are inevitable during infectious disease crises. To support ethical nursing practices, understanding the ethical competencies required in such contexts is essential.ObjectivesThe aim of this study was to explore the phenomenon related to ethical competence among clinical nurses during the COVID-19 pandemic.Research Design, Participants and Research ContextA qualitative explorative approach was used. Data were collected through focus group interviews from 10 clinical nurses working in general and tertiary hospitals in Korea, and analyzed using content analysis.Ethical ConsiderationsThis study was approved by the institutional review board of the university to which the researchers belonged.ResultsThis study derived five core categories—moral solidarity, moral courage, ethical knowledge, ethical decision-making, and ethical reflection—along with their respective components.ConclusionsThis study provides empirical evidence that can contribute to a structured conceptualization of nursing ethical competence for infectious disease crises. Further research is suggested to contribute to practical educational and institutional support to strengthen this competence.